Vulnerability assessments of Colorado ground water to nitrate contamination - Ceplecha, Z., author; Waskom, R., author; Bauder, T., author; Sharkoff, J., author; Khosla, R., author; Water, Air, and Soil Pollution, publisher (Colorado State University. Libraries, 2004)
Nitrate (NO3-N) contamination of ground water aquifers is an important problem in the United States and throughout the world, particularly as ground water resources become increasingly relied upon to support human needs. Cost effective methodologies are needed to facilitate decision-making for ground water protection. To aid ground water protection organizations, we designed two tools to assess aquifer vulnerability to NO3-N contamination in Colorado. The first tool is a statewide aquifer vulnerability map (VM) that identifies regions vulnerable to ground water contamination. The VM uses five factors that influence aquifer vulnerability on a regional scale: aquifer locations, depth to water, soil drainage class, land use, and recharge availability. We validated the VM using 576 discrete ground water sample points from throughout the state and found that the VM was able to delineate areas of increased aquifer vulnerability to NO3-N contamination (r2= 0.78). The second aquifer assessment tool is a vulnerability matrix (VMX) developed to help practitioners determine relative aquifer vulnerability to NO3-N contamination on a field scale. The VMX consists of a series of factors that are rated and combined for a particular field. This rating is used to give landowners an index of general aquifer vulnerability to NO3-N contamination for a specific field, and inform them of changes in management practices to reduce the vulnerability. The VMX can be used in conjunction with the VM to determine NO3-N contamination potential from intensive agriculture.
Keywords: ground water; nitrate leaching; vulnerability; geographic information systems; GISradar; extreme rainfall event